2012
DOI: 10.1038/ejhg.2012.185
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity in Finnish hereditary prostate cancer using ordered subset analysis

Abstract: Prostate cancer (PrCa) is the most common male cancer in developed countries and the second most common cause of cancer death after lung cancer. We recently reported a genome-wide linkage scan in 69 Finnish hereditary PrCa (HPC) families, which replicated the HPC9 locus on 17q21-q22 and identified a locus on 2q37. The aim of this study was to identify and to detect other loci linked to HPC. Here we used ordered subset analysis (OSA), conditioned on nonparametric linkage to these loci to detect other loci linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…The genetics of myopia in Ashkenazi Jewish families has been studied using exome genotyping 56 and genome-wide scanning. 57 Results reveal complex genetic heterogeneity of myopia, even in a genetically isolated population such as Ashkenazi Jews with highly aggregated families, most likely involving many low-penetrance genes combined with environmental factors. All the boys in the current study were Jewish and had similar numbers of myopic parents, despite ultra-Orthodox and religious boys having higher myopia prevalence.…”
Section: Discussionmentioning
confidence: 93%
“…The genetics of myopia in Ashkenazi Jewish families has been studied using exome genotyping 56 and genome-wide scanning. 57 Results reveal complex genetic heterogeneity of myopia, even in a genetically isolated population such as Ashkenazi Jews with highly aggregated families, most likely involving many low-penetrance genes combined with environmental factors. All the boys in the current study were Jewish and had similar numbers of myopic parents, despite ultra-Orthodox and religious boys having higher myopia prevalence.…”
Section: Discussionmentioning
confidence: 93%
“…Since our study was not able to consider genetic heterogeneity due to the limited sample size, larger family-based linkage studies in African Americans should be conducted with the application of more recent developments in linkage methods for complex disease to overcome issues related to disease heterogeneity (45, 46), locus heterogeneity and incomplete penetrance, which can decrease power to detect linkage. Additional family-based recruitment and linkage analyses in a sample with more homogeneous subsets of families will increase the ability to detect linkage.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis is of particular interest because it is suggested that by decreasing the etiologic heterogeneity through the ranking, statistical power to detect linkage is increased (Hauser et al., ). This method has proven successful in identifying linked loci in several disorders including age‐related macular degeneration (Schmidt et al., ) and hereditary prostate cancer (Simpson et al., ).…”
Section: Commentarymentioning
confidence: 99%